HUBUNGAN ASUPAN KALSIUM DAN KONSUMSI MINUMAN RINGAN BERKARBONASI DENGAN MASSA TULANG MAHASISWA S1 UGM YOGYAKARTA - , MONICA NOVARA HARDINI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : Osteoporosis known as silent disease, attacks silently without specific signs until a fracture occurs. Data analysis that was conducted on the risk of osteoporosis in 2005 showed the prevalence of osteopenia was 41,7% and the prevalence of osteoporosis was 10,3% which 41,2% of the total sample that were aged under 55 years old was diagnosed with osteopenia. This report shows that 2 out of 5 Indonesian people are at risk of developing osteoporosis, and this problem are increasing at youth. Bone mineral density can be influenced by daily calcium intake and consumption of carbonated soft drinks. Objective : to determine the correlation between calcium intake and consumption of carbonated soft drinks with bone mass. Methods : observational, cross-sectional design. The subject was 94 undergraduated students that was selected through purposive sampling. Results : Based on the results of the study, 74,5% of the subject had normal bone mass. Subjects who didnât achieve daily calcium requirement (<800 mg/day) as much as 77,7%. Average subjectâs calcium intake 500,05 mg/day. Subjects who consumed carbonated soft drinks in one last month as much as 59,57%. Average subjectâs consumption of carbonated soft drinks as much as 12,1 ml/day. Statistical test results showed no association of calcium intake with bone mass (p=0,859). There is no correlation between consumption of carbonated soft drinks with bone mass (p=0,442). Conclusion